2016
DOI: 10.1007/s00423-016-1529-6
|View full text |Cite
|
Sign up to set email alerts
|

Preserving infrapyloric vein reduces postoperative gastric stasis after laparoscopic pylorus-preserving gastrectomy

Abstract: Preservation of the IPV might prevent the incidence of postoperative gastric stasis after LPPG, resulting in a shorter postoperative stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 18 publications
3
25
0
Order By: Relevance
“…This procedure has been routinely performed by most surgeons. Kiyokawa published another report concluding that preservation of infrapyloric vein would further reduce the incidence of gastric stasis [27]. To our knowledge, this present study reports the lowest prevalence of delayed gastric emptying following PPG.…”
Section: Discussionsupporting
confidence: 45%
“…This procedure has been routinely performed by most surgeons. Kiyokawa published another report concluding that preservation of infrapyloric vein would further reduce the incidence of gastric stasis [27]. To our knowledge, this present study reports the lowest prevalence of delayed gastric emptying following PPG.…”
Section: Discussionsupporting
confidence: 45%
“…Patients who underwent PPG sometimes report the feeling of gastric fullness, and some patients exhibit long-term retention of food in the residual stomach; however, some investigators claim that the vagal nerve and the infrapyloric artery should be preserved to prevent postoperative stasis, which is experienced by 6% to 8% of the patients (7,11). Specifically related to the rate of gastric stasis after LAPPG, the infrapyloric vein should prevent pyloric cuff edema, thus minimizing the incidence of gastric stasis; a study indeed investigated early clinical outcomes of LAPPG with preservation of the infrapyloric vein, not only infrapyloric artery (28). The incidence of both gastric stasis and transient delayed gastric emptying was significantly lower in patients who underwent LAPPG that preserved the infrapyloric artery and vein than in those who underwent LAPPG without the preservation of the infrapyloric vein.…”
Section: Gastric Stasis After Ppgmentioning
confidence: 99%
“…Moreover, it is well-known that the vagal nerves such as PHCV are an important factor in intestinal peristalsis [20]. In addition, it is reported that preservations of the infrapyloric artery and vein are important to prevent the postoperative gastric stasis after PPG [15] [16]. Ischemia around pylorus may lead to pyloric dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…PGD such as malnutrition due to loss of appetite, weight loss, EDS, RE, or GRS are unfavorable sequelae in patients after conventional It is considered that PGD, especially PAF with GSRS, after PPG is due to damage to PHCV and infrapyloric vesscels (artery and vein) as a result of skeletonization of the subpyloric region with the subpyloric lymph node dissection [15] [16]. It is also reported that PHCV are necessary for pyloric sphincter functioning in patients after PPG [11] [12].…”
Section: Discussionmentioning
confidence: 99%